(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the stylistic challenges faced by translators in the process of converting texts from one language to another. It highlights various issues, including cultural differences, tone and register, connotative versus denotative meaning, wordplay, and the preservation of literary style. The article also addresses the difficulties of maintaining consistency in technical terminology and adapting sentence structure across languages. It emphasizes the importance of creativity, cultural awareness, and linguistic sensitivity in ensuring that a translation accurately conveys the original text’s meaning, while remaining stylistically appropriate for the target audience. Ultimately, the article underscores the pivotal role of translators in bridging linguistic and cultural gaps.